ANALISIS WILLINGNESS TO PAY MASYARAKAT TERHADAP PENGADAAN LAYANAN PDAM TIRTA RAHARJA MENGGUNAKAN METODE CONTINGENT VALUATION - Raihana, Farah Fauzia (CREATIVE RESEARCH JOURNAL, 2020)
Gandasari is one of the villages in Katapang Sub District, Bandung Regency. Most people in Gandasari Village use groundwater as their main water source to fulfill their needs of water. Groundwater in Gandasari Village has bad quality and quantity. Hence, the provision of a safe water supply is needed in Gandasari Village. On the other hand, Perusahaan Daerah Air Minum (PDAM) Tirta Raharja is developing their House Connection (SR) in Gandasari Village RW 5,6,7,9, and 11. Provision and management of water supply required to achieve full cost recovery. Therefore, it is necessary to know the willingness to pay (WTP) value for the provision of PDAM’s pipe connection. This study aimed to determine households’ WTP for the provision of piped water service and identify the factors affecting it. The WTP was estimated through questionnaires collected from 89 households in Gandasari Village using Contingent Valuation Method (CVM) and bidding games technique. Based on the questionnaire result, the Estimated Mean WTP (EWTP) value of WTP for installation fee is Rp961.798 and Total WTP is Rp735.775.281. Meanwhile the EWTP value of WTP for retribution fee is Rp51.180/month and TWTP is Rp39.152.528. Factors affecting the value of WTP for installation fee is household size and average income, meanwhile for retribution fee WTP value average income was the affecting factor. Provision of communal well is recommended for households who cannot afford to pay for PDAM.